2008
DOI: 10.1177/1524838008315869
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive–Behavioral Theory and Preparation for Professionals at Risk for Trauma Exposure

Abstract: Military personnel, emergency first responders, and others whose work environments include exposure to traumatic events are at risk for developing posttraumatic stress disorder (PTSD). To help prevent negative sequelae, there is a strong need to identify well-operationalized, empirically supported, theoretically framed models of healthy adaptation to potentially traumatic events. Cognitive-behavioral theories (CBTs) describe etiological factors in trauma, guide research that has identified risk for PTSD, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 98 publications
5
67
0
1
Order By: Relevance
“…While the research is not longitudinal and cannot speak to causation, it appears that those who are more burned out are more likely to report PTSD symptoms. It is also possible that, consistent with previous findings (Whealin et al 2008), PA, which could represent a form of perceived self-efficacy, may serve as a buffer for the development of PTSD symptoms. Thus, emphasizing accomplishment in relief work may be beneficial to the mental health of workers and ultimately to the long-term effectiveness of aid work.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…While the research is not longitudinal and cannot speak to causation, it appears that those who are more burned out are more likely to report PTSD symptoms. It is also possible that, consistent with previous findings (Whealin et al 2008), PA, which could represent a form of perceived self-efficacy, may serve as a buffer for the development of PTSD symptoms. Thus, emphasizing accomplishment in relief work may be beneficial to the mental health of workers and ultimately to the long-term effectiveness of aid work.…”
Section: Discussionsupporting
confidence: 79%
“…Cognitive behavioral interventions that show promise in fostering resilience in the face of trauma exposure include enhancing appraisal styles, positive reframing and coping mechanisms as well as increasing perceived self-efficacy (Whealin et al 2008). While these interventions demonstrate effectiveness across various ethnic and international groups, it is also important to document support needs within the language and framework of a culture in order to develop interventions that are culturally specific and relevant for that context.…”
Section: Resilience and Humanitarian Aid Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Taken together, these findings underscore the importance of cognitive-behavioral interventions that promote perceptions of control and self-efficacy, encourage positive appraisals and acceptance of change, and increase adaptive coping strategies in individuals with PTSD. [29] One example of such an intervention is well-being therapy, which focuses on enhancing personal growth, purpose in life, autonomy, selfacceptance, and positive relations with others, and has been shown to improve symptoms associated with mood and anxiety disorders. [30] Postdeployment social support was also negatively associated with traumatic stress and depressive symptoms, which suggests that efforts to enhance social support and help veterans learn how to seek out social support may be effective in reducing the negative impact of traumatic stress.…”
Section: Discussionmentioning
confidence: 99%
“…The only study to demonstrate that self-reported social support was associated with improved PTSD treatment response was conducted with a civilian sample (Thrasher, Power, Morant, Marks, & Dalgleish, 2010). Although members of the social support network are not directly involved in treatment, it is expected that increased support outside of treatment will enhance response due to the protective effect of social support on PTSD symptoms (Barrett & Mizes, 1988; Whealin et al, 2008). …”
mentioning
confidence: 99%